A Shape-Variable, Low-Temperature Liquid Metal-Conductive Polymer Aqueous Secondary Battery - Fu, Hao; Liu, Guicheng; Xiong, Lingyun; Wang, Manxiang; Lee, Jeongwoo; Ren, Ren; Yang, Woochul; Lee, Joong Kee (WILEY-V C H VERLAG GMBH, 2021)
A shape-variable aqueous secondary battery operating at low temperature is developed using Ga68In22Sn10 (wt%) as a liquid metal anode and a conductive polymer (polyaniline (PANI)) cathode. In the GaInSn alloy anode, Ga is the active component, while Sn and In increase the acid resistance and decrease the eutectic point to -19 degrees C. This enables the use of strongly acidic aqueous electrolytes (here, pH 0.9), thereby improving the activity and stability of the PANI cathode. Consequently, the battery exhibits excellent electrochemical performance and mechanical stability. The GaInSn-PANI battery operates via a hybrid mechanism of Ga3+ stripping/plating and Cl- insertion/extraction and delivers a high reversible capacity of over 223.9 mAh g(-1) and an 80.3% retention rate at 0.2 A g(-1) after 500 cycles, as well as outstanding power and energy densities of 4300 mW g(-1) and 98.7 mWh g(-1), respectively. Because of the liquid anode, the battery without packaging can be deformed with a small force of several millinewtons without any capacity loss. Moreover, at approximately -5 degrees C, the battery delivers a capacity of 67.8 mAh g(-1) at 0.2 A g(-1) with 100% elasticity. Thus, the battery is promising as a deformable energy device at low temperatures and in demanding environments.
Keywords: LITHIUM-ION BATTERIES; HIGH-VOLTAGE; SURFACE MODIFICATION; AIR BATTERY; CARBON; ELECTRODE; FIBERS; ANODE; SUPERCAPACITOR